Providing dental services where there are no roads: Lessons from the field - Kuldeep Singh Shekhawat; Sanjoy Hazarika; Arunima Chauhan; Ashok Rao (Wolters Kluwer Medknow Publications, 2020)
Background: The riverine islanders of Brahmaputra (Assam, India) are among the most economically backward population group of Assam. Recurring floods results in eclectic damage affecting their everyday lives. Medical Relief is limited due to vast water body, which pose a challenge in providing and accessing health services with limited or no provision for oral health services. Objectives: Planning and implementing a program for delivery of dental services on an already existing model of 'Boat Clinics' in Assam, India. Setting and Design: Isolated riverine islands of Brahmaputra River in North eastern State of Assam, India. Materials and Methods: A service model was designed to implement and provide dental services on an already existing model of 'Boat Clinics' in Assam. Dentals services were provided via two dental units installed (in March 2016) in two different boats on a trial basis. Situation analysis of the setting was done prior to implementation. Challenges encountered were overcome using alternative strategy. Results: Situation analysis revealed dental caries affecting about 59.8 percent of the islanders (DMFT=3). The number of beneficiaries almost doubled from 2016. More than 750 islanders have been treated in 2017 from one 'boat dental clinic'. Women seem to utilize oral health services more than men and extraction was preferred over restoration. The main challenge had been the unavailability of full time dentists, auxillary dental personnel and management of complex dental cases. Discussion: Boat Dental Clinic Program is in accordance with objectives of National Oral Health Program. Corporate social Responsibility is excellent option that provide resources instrumental in initiating projects and more importantly sustaining them. Public Private Not for Profit Partnership (PPNP) is another way to bridge the disparity in the present setting having a downstream effect at the grass root level.